Impact of Climate Change on Spider Species Distribution Along the la Plata River Basin, Southern South America: Projecting Future Range Shifts for the Genus Stenoterommata (Araneae, Mygalomorphae, Nemesiidae) - Ferretti, Nelson Edgardo (2018)
The La Plata River basin comprises the second largest fluvial system in South America and includes the southernmost remains of the "Atlantic Forest Biodiversity Hotspot". We used species distribution modelling to evaluate potential effects of climate change on six species of Stenoterommata. Changes in the size of suitable climatic regions and numbers of known occurrence sites were evaluated within the distribution limits of the studied species. We used MaxEnt (program for modelling species distributions from presence-only species records) to predict current and future suitable areas. Two representative concentration pathways (RCP6.0 and RCP8.5) that represent different greenhouse gas concentration trajectories were modelled for the years 2050 and 2070. The isothermality, temperature seasonality and variation in seasonal precipitation were found to be the top three variables that affect the range of Stenoterommata species. Highly suitable habitat was found to increase with time for most species, except for S. platensis, whose distribution area may shrink by more than 50% by the year 2070.